Modified hollow mesoporous silica nanoparticles as immune adjuvant-nanocarriers for photodynamically enhanced cancer immunotherapy - Li, Qianru; Liu, Qianqian; Li, Heli; Dong, Liyun; Zhou, Yajie; Zhu, Jintao; Yang, Liu; Tao, Juan (Frontiers in Bioengineering and Biotechnology, 2022)
Nanomedicine has demonstrated great potential in enhancing cancer immunotherapy. However, nanoparticle (NP)-based immunotherapy still has limitations in inducing effective antitumor responses and inhibiting tumor metastasis. Herein, polyethylenimine (PEI) hybrid thin shell hollow mesoporous silica NPs (THMSNs) were applied as adjuvant-nanocarriers and encapsulated with very small dose of photosensitizer chlorine e6 (Ce6) to realize the synergy of photodynamic therapy (PDT)/immunotherapy. Through PEI etching, the obtained Ce6@THMSNs exhibited enhanced cellular internalization and endosome/lysosome escape, which further improved the PDT efficacy of Ce6@THMSNs in destroying tumor cells. After PDT treatment, the released tumor-associated antigens with the help of THMSNs as adjuvants promoted dendritic cells maturation, which further boosted CD8+ cytotoxic T lymphocytes activation and triggered antitumor immune responses. The in vivo experiments demonstrated the significant potency of Ce6@THMSNs-based PDT in obliterating primary tumors and inducing persistent tumor-specific immune responses, thus preventing distant metastasis. Therefore, we offer a THMSNs-mediated and PDT-triggered nanotherapeutic system with immunogenic property, which can elicit robust antitumor immunity and is promising for future clinical development of immunotherapy.